Analisa Fitokimia dan Aktivitas Antioksidan Sirup Herbal Ekstrak Buah Labu (Curcubita Moschata) dan Rimpang Kunyit (Curcuma Domestica) dengan Metode DPPH - Kurniasih, Khamdiyah Indah; Fauziah, Fauziah; Misworo, Misworo; Prismadito, Hansen (Journal of Pharmaceutical and Health Research, 2025)
Pumpkin is one of the natural ingredients with antioxidant properties, and it helps reduce symptoms of diabetes, hypertension, tumors, cholesterol, antibacterial, anthelmintic, and anti-inflammatory effects. The polyphenol and flavonoid contents in pumpkin are 97.4 mgGAE/gram and 28.6 mgQE/gram, respectively, with high antioxidant activity against DPPH radicals at 0.065 ± 0.010 mol TE/gram. Turmeric rhizome is also a plant with high antioxidant activity. Turmeric rhizome contains curcumin as the main active compound, with a content of 7.798%. The ethanol extract of turmeric rhizome exhibits antioxidant activity with an IC50 value of 41.95 µg/mL (DPPH). Studies on the composition and benefits of pumpkin and turmeric rhizome have been conducted. However, so far, there has been no standardization of the simplicia and extracts of these two plants from Central Java. The herbal syrup combining pumpkin and turmeric extracts is an herbal product that has not been scientifically proven regarding its metabolite compounds and antioxidant activity, which play a role in addressing various degenerative diseases. Therefore, standardization of the simplicia and verification of the phytochemical metabolites and antioxidant content are necessary. This study was conducted by comparing the IC50 values of three syrup formulas: turmeric rhizome syrup (F1), pumpkin syrup (F2), and a mixture of pumpkin and turmeric rhizome syrup (F3). The results showed that Formula 1 (F1) had the lowest IC50 value of 17.366 µg/mL, indicating the highest antioxidant potential, followed by F3 with an IC50 of 47.862 µg/mL, and F2 with the lowest antioxidant activity, with an IC50 value of 288.545 µg/mL.